ANALISIS FAKTOR KEAMANAN LINGKUNGAN DALAM STRATEGI DINAS PERHUBUNGAN GUNA MENGATASI PELANGGARAN PARKIR DI ALUN-ALUN KOTA BANDUNG - Carolos, Roland; Kurniati, Poni Sukaesih (JURISMA : Jurnal Riset Bisnis & Manajemen, 2021)
ABSTRACT The purpose of this research is to know how the environmental security factor analysis in the strategy of transportation service in overcoming wild parking at Alun-Alun Bandung city. The method used in this research is a qualitative, desktiptive approach, a qualitative approach chosen by researchers because the objects examined by the thicning are not numeric objects but rather this research is conducted based on the use of reasoning with researchers as instruments. Wild parking problem in Alun-alun Bandung disrupts traffic activity and citizen about Alun-Kota Bandung, where, despite the provided basement parking facility, wild parking is still there. The result of this research is the wild parking around the square-Allun Badnung city still exists, dfaith with all the efforts that have been done is still not also cause a deterrent effect against wild parking actors, therefore researchers hope that the Ministry of Transportation continues to try to find a way to provide effective deterrent effects. Keywords: environment, square, wild parking, Bandung city.